Some Factors Influencing Watersheds - Qureshi, I. M.; Yadav, J. S. P. (Indian Forester, 1966)
The water balance of watersheds involving the losses due to interception, run-off, evaporation, transpiration, underground drainage and the gains due to storage as soil moisture has been discussed. It has been shown that floods take place mainly due to the excess of precipitation over the absorbing capacity of the soil. The changes in moisture content below the soil surface and the effect of these changes on run-off, floods and stream flow are depicted. The effect of various edaphic factors, namely soil texture, structure, depth, organic matter content, character of subsoil, water table, geology and topography on infiltration, percolation and storage capacity as well as on water movement and hydrology of a given area has been brought out clearly. The influence of burning, grazing, mechanical compaction, shifting cultivation, faunal activity. etc., on the soil properties and moisture relations of watersheds has also been dealt with. Important features and analytical data of a few major soil groups found in India have been presented and correlated with their moisture characteristics. The effects of different vegetative covers on the soil mnisture dynamics and water yield have been described, and the value of maintenance of a suitable vegetative cover on the catchment area and creation of conditions conducive to adequate percolation and infiltration in the soil has been emphasized. It has been mentioned that soil moisture studies provide a useful diagnostic basis for understanding the water balance of a catchment area. In view of the magnitude and complexity of the problem need for well planned research has been suggested.